Safeguarding Auditors’ Independence When Performing Audit and Non-Audit Services: Evidence from Indonesian Audit Firm - Indah Solagracia Arie Tiranda; Agung Juliarto (Diponegoro Journal of Accounting, 2021)
The purpose of conducting an audit is to give an independent opinion whether the financial report’s detail accurately represents the organization’s financial situation. In performing his job, auditors should be independent from their client company, so that the audit opinion will not be affected by any kind of relationship between auditor and client. Auditors should be able to carry out their job and give an unbiased opinion on the financial statements to shareholders. In this way the auditors are considered that they can carry out their job in objective way. On the other hand, there are many auditors who not only perform audit services but also non-audit services. In this case there is a possibility that their independence is impaired because there is an implicit intention. When performing the dual service, auditors face many threats that come from the outside or even inside which is themselves. The regulation of performing their job is the guideline for auditors, but they will always their own decision and responsibility which put their integrity and morality on the line. Therefore, this paper aims to find the key factors on safeguarding auditors’ independence in which their integrity and morality when performing dual service by explaining the threats, advantages and disadvantages, the physiological effect towards the behaviour of auditors of performing both services, and the integrity and morality itself when carrying out their job. The researcher used interviews to obtain more available and reliable information from experts in this field. The researcher also used a literature review method by accessing article through search engine to create this research.